Hereditary breast cancer risk gene assessment and counseling: interpretation of NCCN guidelines and Ruijin Hospital clinical practice - HAN Mengyuan, CHEN Xiaosong (Waike lilun yu shijian)
Hereditary breast cancer-related gene mutations significantly increase the risk of breast cancer in women. In this regard, the National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines in Genetic/Familial High-Risk Assessment was developed to guide genetic assessment and counseling in mutation carriers of breast cancer risk genes, providing crucial information for the prevention, screening and treatment of breast cancer. This article provided an interpretation of the NCCN Clinical Practice Guidelines in Genetic/Familial High-Risk Assessment, integrating the clinical practice experience of Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine.